Mid-regional pro-atrial natriuretic peptide as a biomarker of left ventricular systolic dysfunction in patients with sepsis (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND Releasing cytokine pro inflammation in patients with sepsis (tumor necrosis factor-alpha (TNF-α), interleukin-1β (IL-1β) and IL-6) with other factors (mid regional pro atrial natriuretic peptide [MR-proANP] and TNF-α) will cause left ventricular systolic dysfunction (LVSD). This research aimed to prove MR-proANP as a biomarker of LVSD in sepsis, area under the curve (AUC), sensitivity, specificity, cut-off point and probability of MR-proANP and TNF-α as a biomarker of LVSD. METHODS Non-experimental diagnostic test with cross sectional design and simple random sampling. Variable examined consisted of MR pro ANP, TNF-α and left ventricular ejection fraction (LVEF). LVSD if LVEF was ≤45%. Statistical analysis using 2 x 2 table and receiver operating characteristic curve using SPSS 22 for window. RESULTS There were examined 71 patients from November 2013 to March 2014 in tertiary ICU of Moewardi Hospital. There were 22 patients with mild sepsis (30.9%), 40 patients with severe sepsis (56.4%) and 9 patients with septic shock (12.7%). The AUC value of MR-proANP level was 0.84 (95% CI 0.73-0.95), p < 0.001. Optimal cut off point was ≥225.95 pmol/l and diagnostic odd ratio (DOR) was 12.11. The AUC value of TNF-α level was 0.73 (95% CI 0.60-0.86), p < 0.002. Optimal cut-off point was ≥7.36 pg/ml and DOR was 5.03. Multivariate analysis was resulted that MR-proANP was the best predictor of LVSD (AUC 0.78), and TNF-α (0.69). CONCLUSIONS MR-proANP could be used as a biomarker and the best diagnostic predictor of LVSD.